Use Case - Delivering Contextualized Climate Information in two Districts of Odisha and Understanding Farmer Decision-Making: A case study in Odisha - Kumar, Shalander; Kumar, G. Kishore; Roa, K.P.C. (International Food Policy Research Institute, 2024)
Smallholder agriculture, especially in the global South, is highly vulnerable to climate variability and change; hence, the aim of the Digital Innovation initiative was to equip farmers with actionable weather-based agro advisories to improve farm management and mitigate climate risks. This working paper explores the delivery of contextualized climate information to farmers in Rayagada and Gajapati districts of Odisha. The region is characterized by predominantly rainfed agriculture and high vulnerability to climate variability. The objective was to enhance farmers' resilience by providing tailored climate advisories and understand the dynamics of their decision-making across various farming stages while using agro advisories. A mixed-methods approach was employed, involving surveys with 200 farmers across four blocks of two districts and focus group discussions to gather comprehensive insights into their decision-making processes. The study found that 79% of farmers were male, while 21% were female, highlighting the need for gender-sensitive advisories. Decision-making was influenced by a complex interplay of traditional knowledge, market dynamics, climate advisories, and social influences. Digital climate services, such as those offered by ISAT, have shown to be valuable, with 82% of farmers accessing these advisories. Adoption rates varied significantly across different farming activities, with 67% adoption for supporting crop sowing decisions and 69% for crop protection, compared to lower uptake in land preparation (29%) and irrigation (24%). For decisions on crop and cultivar choice, farmers didn’t intend to use the weather-based agro-advisories yet. Probably, advisories based on the seasonal climate forecast needed for decisions on crop and cultivar choices in the past either were not available or less reliable, resulting in the reluctance of farmers to use such advisories. The findings suggest that climate advisory services should be more localized, culturally sensitive, and integrated with traditional practices to address farmers' diverse needs effectively. By bridging the gap between modern advisory systems and traditional wisdom, these integrated services have the potential to enhance farm-level resilience and contribute meaningfully to the livelihoods of smallholder farmers in Odisha.